ANALYSIS OF ISLAMIC BUSINESS STRATEGY IN INCREASING SALES OF SYAR'I CLOTHING PRODUCTS CASE STUDY OF MICKEY OLSHOP BOUTIQUE TEBING TINGGI - Laluna Luthfyadha Harirra; Santi Arafah (CV. Radja Publika, 2026)
This study aims to analyze the Islamic marketing strategy implemented by Mickey Olshop Muslim Fashion Store in Tebing Tinggi to increase sales of sharia clothing products. The research also examines the advantages and disadvantages of implementing Islamic marketing strategies, as well as the supporting factors and obstacles faced in their application. This qualitative research was conducted over five months at Mickey Olshop Tebing Tinggi Boutique. Data collection methods included observation, in-depth interviews with the store owner, assistant manager, and employees, as well as documentation. The findings reveal that Mickey Olshop implements an Islamic marketing strategy through several approaches: promotional activities with discounts ranging from 10-30% during Islamic holidays, prioritizing excellent customer service with polite and courteous treatment, requiring employees to wear Muslim clothing to showcase product quality, offering discounts on defective products, operating a dropshipping system based on the principle of mutual assistance (ta'awun), and utilizing an online marketing system through an official website. The advantages of this strategy include facilitating business entry without capital requirements, strategic location accessibility, diverse product offerings, and authentic quality products that compete effectively with other Muslim fashion stores. However, disadvantages include limited customization options, consumer perceptions that associate robes with religious exclusivity, non-Sharia compliant products in some items, stock limitations due to imported goods, and relatively high prices. Supporting factors include positive customer feedback, good management, honest employees, and excellent service standards. Obstacles comprise limited parking space, proximity to congested main roads, relatively expensive products limiting purchasing power, and delays in imported goods delivery.